Autorzy:Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Przedstaw wyrażenie w postaci sumy algebraicznej.4.33 gwiazdek na podstawie 6 opinii

Przedstaw wyrażenie w postaci sumy algebraicznej.

14Zadanie
15Zadanie
16Zadanie

`a) \ \ (7m-3)^2=(7m)^2-2*7m*3+3^2=49m^2-42m+9`

`b) \ \ (3t-9p)^2=(3t)^2-2*3t*9p+(9p)^2=9t^2-54tp+81p^2`

`c) \ \ (6z-2/3)^2=(6z)^2-2*strike6^2z*2/strike3^1+(2/3)^2=36z^2-8z+4/9`

`d) \ \ (20-0,9s)^2=20^2-2*20*0,9s+(0,9s)^2=400-36s+0,81s^2`

`e) \ \ (t-sqrt3)^2=t^2-2*t*sqrt3+(sqrt3)^2=t^2-2sqrt3t+3`

`f) \ \ (sqrt2-ysqrt8)^2=(sqrt2)^2-2*sqrt2*ysqrt8+(ysqrt8)^2=2-2sqrt16y+y^2*(sqrt8)^2=`

`=2-2*4y+8y^2=2-8y+8y^2`